Proceedings of Annual Workshop 2024 with the Partners on Mixed Farming Systems (MFS) Initiative in Bangladesh - Haque, Abdul; Kamal, Mustafa; Humaira Sadaf, Bushra; Ahmed, Sharif; Mponela, Powell; Bhandari, Humnath (International Rice Research Institute, 2024)
The Annual Workshop on CGIAR initiative on Mixed Farming Systems (MFS) was held from 29-30 October 2024 at Kuakata, Patuakhali, Bangladesh. The workshop aimed to promote sustainable agricultural practices through the integration of crops, livestock, and agroforestry to optimize both ecological and economic outcomes. This event gathered key stakeholders from several prominent agricultural research institutions, including the Bangladesh Rice Research Institute (BRRI), Bangladesh Agricultural Research Institute (BARI), Bangladesh Livestock Research Institute (BLRI), and the International Maize and Wheat Improvement Center (CIMMYT). The workshop focused on the review of ongoing research, accomplishments, and the future direction of sustainable agricultural practices to enhance food security and resilience in Bangladesh's mixed farming systems.